Neuroinflammatory and morphological changes in late-life depression: the NIMROD study. (December 2016) - Su, Li; Faluyi, Yetunde O.; Hong, Young T.; Fryer, Tim D.; Mak, Elijah; Gabel, Silvy; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy B.; Arnold, Robert; Passamonti, Luca; Rodríguez, Patricia Vázquez; et al.
Summary: We studied neuroinflammation in individuals with late-life, depression, as a risk factor for dementia, using [ 11 C]PK11195 positron emission tomography (PET). Five older participants with major depression and 13 controls underwent PET and multimodal 3T magnetic resonance imaging (MRI), with blood taken to measure C-reactive protein (CRP). We found significantly higher CRP levels in those with late-life depression and raised [ 11 C]PK11195 binding compared with controls in brain regions associated with depression, including subgenual anterior cingulate cortex, and significant hippocampal subfield atrophy in cornu ammonis 1 and subiculum. Our findings suggest neuroinflammation requires further investigation in late-life depression, both as a possible aetiological factor and a potential therapeutic target.